Catalina, ROMERO e Ismael, MUÑOZ (eds.). (1993). Liberación y Desurro-110 en América Latina, Lima, Instituto Bartolomé de las Casas - C.E.P. - Vega-Centeno, Máximo (1993)
Esta reseña no presenta resumen.